Endothelial Cell-Specific Molecule-1 in Critically Ill Patients With Hematologic Malignancy. Issue 3 (March 2018) - Zafrani, Lara; Resche-Rigon, Matthieu; De Freitas Caires, Nathalie; Gaudet, Alexandre; Mathieu, Daniel; Parmentier-decrucq, Erika; Lemiale, Virginie; Mokart, Djamel; Pène, Frédéric; Kouatchet, Achille; Mayaux, Julien; Vincent, François; et al.
Abstract : Objectives: To assess whether serum concentration of endothelial cell-specific molecule-1 (Endocan) at ICU admission is associated with the use of ICU resources and outcomes in critically ill hematology patients. Design: Prospective multicenter cohort study. Setting: Seventeen ICUs in France and Belgium. Patients: Seven hundred forty-four consecutive critically ill hematology patients; 72 critically ill septic patients without hematologic malignancy; 276 healthy subjects. Intervention: None. Measurements and Main Results: Median total endocan concentrations were 4.46 (2.7–7.8) ng/mL. Endocan concentrations were higher in patients who had received chemotherapy before ICU admission (4.7 [2.8–8.1] ng/mL vs. 3.7 [2.5–6.3] ng/mL [ p = 0.002]). In patients with acute respiratory failure, endocan levels were increased in patients with drug-induced pulmonary toxicity compared with other etiologies ( p = 0.038). Total endocan levels higher than 4.46 ng/mL were associated with a higher cumulative probability of renal replacement therapy requirement ( p = 0.006), a higher requirement of mechanical ventilation ( p = 0.01) and a higher requirement of vasopressors throughout ICU stay ( p < 0.0001). By multivariate analysis, total endocan levels at admission were independently associated with ICU mortality (odds ratios, 1.39; 95% CI, 1.06–1.83; p = 0.018). The predictive value of endocan peptide fragments of 14 kDa in terms of mortality and life-sustaining therapies requirement was inferior to that of total endocan. Endocan levels were higher in critically ill hematology patients compared with healthy subjects ( p < 0.0001) but lower than endocan values in critically ill septic patients without hematologic malignancy ( p = 0.005) Conclusions: Serum concentrations of endocan at admission are associated with the use of ICU resources and mortality in critically ill hematology patients. Studies to risk-stratify patients in the emergency department or in the hematology wards based on endocan concentrations to identify those likely to benefit from early ICU management are warranted. Abstract : Supplemental Digital Content is available in the text.